Leveraging a Genetic Proxy to Investigate the Effects of Lifelong Cardiac Sodium Channel Blockade - Wanner, Julian S.; Krafft, Maren; Niiranen, Teemu; Zimmerman, Dominic S.; Ellinor, Patrick T.; Nadkarni, Girish; Jurgens, Sean J.; Rämö, Joel; Heyne, Henrike O. (Lippincott, 2026)
BACKGROUND:
Atrial fibrillation and other cardiac arrhythmias pose a major public health burden, but prevention remains difficult. We investigated a genetic variant that we found to act like a natural lifelong cardiac sodium channel blockade.
METHODS:
We studied the impact of the Finnish-enriched SCN5A missense variant (rs45620037 [T220I]) on cardiac arrhythmias, associated mortality, and ECG phenotypes in a multicohort observational study with >1 million individuals across 3 cohorts (FinnGen, UK Biobank, and Health 2000).
RESULTS:
We identified protective effects of T220I on multiple common cardiac arrhythmias, most notably atrial fibrillation (cause-specific hazard ratio [HR], 0.56 [95% CI, 0.50–0.63]; P<0.0001), but also ventricular premature depolarization or ventricular tachycardia, as well as increasing susceptibility to conduction-slowing conditions, such as sick sinus syndrome (mostly in older age groups). Overall, T220I conveyed protection from death resulting from cardiac arrahajournals.org/jouhythmia (HR, 0.65 [95% CI, 0.46–0.92]; P=0.015) without a significant effect on overall mortality risk (HR, 0.92; P=0.27). T220I heterozygosity had similar electrophysiological effects as some pharmacological sodium channel blockers, such as significantly shortening QT intervals (−7.49 ms [95% CI, −10.07 to −4.91] ms; P=0.0037; n=3188) in the Health 2000 cohort, which we replicated in the UK Biobank (n=66 616). In addition, T220I protected from (left) heart failure and dilated cardiomyopathy. After myocardial infarction, we found that T220I increased mortality risk, consistent with known sodium channel blocker effects, which, however, normalized to baseline 10 to 15 years after myocardial infarction. We found that T220I could lower a high genetic burden (ie, a high polygenic score) for atrial fibrillation to population average.
CONCLUSIONS:
The SCN5A T220I variant, consistent with a previously described weak loss-of-function effect, acted like a genetic proxy for cardiac sodium channel blockade. This enabled us to gain new potentially clinically relevant insights for pharmacological sodium channel blockade, such as after myocardial infarction, which would be too risky to investigate with clinical trials. Our findings may also inspire redesign of cardiac sodium channel blockers.